Investigation On Adsorption Performance Of Mesoporous Activated Biomass Prepared From Cocos Nucifera Husk For Harzadous Cyanide Wastewater Treatment - Yavini, T. D.; Yunusa, M. H.; Atiku, K. G.; Musa, A. A.; Ruth, P. K. (University of Eloued جامعة الوادي, 2017)
The influence of various factors namely pH, absorbent dosage; contact time and initial ion concentration was studied to identify the adsorption capacity of the adsorbent. The optimum pH was obtained at pH =3 for all the adsorbent. Other physiochemical parameters, ranging from the surface area to the scanning electron microscope (SEM) were studied and indicate that the cocos nucifera husk is a good precursor for investigation on activated biomass for hardzadous cyanide wastewater. Adsorption data were modeled using Langmuir, Freundlich, Temkin, Henry and Harkin Jura equation. Henry with the correlation coefficient R2 0.875 had a better fit than Freundlich which is R2= 0.836, Temkin; R2= 0.875, Langmuir; R2= 0.742 and Harkin Jura which is R2= 0.471 with maximum monolayer saturation capacity of cyanide ions adsorbed per gram of activated Cocos nucifera husk. Equibrium data were best described by Henry model. Kinetic models were also carried out including pseudo first order with R2= 0.969, Pseudo-second order R2 = 0.998, Intra-particle diffusion R2 = 0.909, and Elovich Kinetic model with R2 of 0.814, the kinetic data were best described and seen by Pseudo second order model. It is then proven that the study of the entire adsorbent are most efficient for the removal of cyanide from waste waters and it can be used as low-cost adsorbent for the removal of cyanide ions from wastewater.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Cocos nucifera, Kinetics, Adsorbent, Models, Wastewater, Cyanide Ions.